Global Food 50/50 Launch of the Inaugural Report - Njuki, Jemimah; Tanaka, Sonja (2021)
Jemimah Njuki and Sonja Tanaka POLICY SEMINAR Global Food 50/50: Inaugural report on gender, diversity and power in the global food system Co-Organized by IFPRI and Global Health 50/50 OCT 5, 2021 - 08:00 AM TO 09:30 AM EDT